Disproportional makeup of American prisons - Paz, Joseph (Kansas State University. K-State Libraries, 2014)
An examination of the racial makeup of American prisons, this project is a four page paper written in memo format. In an attempt to explain why African Americans make up such a large percentage of federal prisoners, "Disproportional Makeup of American Prisons" examines likely causes for the shocking statistics revolving around race and the United States Prison system. In this paper, I look at how race effects sentencing in regards to the number of African Americans brought to court, the number of African Americans convicted, and the difficulty African Americans face in escaping the cyclical prison system that cripples their potential to succeed in the same society that locked them away in the first place.
Citation: Paz, J. (2014). Disproportional makeup of American prisons. Unpublished manuscript, Kansas State University, Manhattan, KS.Kirmser Undergraduate Research Award - Individual Freshman category, grand prize
Keywords: Race; African Americans; United States prison systems; Inequality; Prejudice